Proportions of Maxillary Anterior Teeth Relative to Each Other and to Golden Standard in Tabriz Dental Faculty Students - Fereydoun Parnia; Ali Hafezeqoran; Farhang Mahboub; Elnaz Moslehifard; Rodabeh Koodaryan; Rosa Moteyagheni; Fariba Saleh Saber (Tabriz University of Medical Sciences, 2010)
Background and aims. Various methods are used to measure the size and form of the teeth, including the golden proportion, and the width-to-length ratio of central teeth, referred to as the golden standard. The aim of this study was to evaluate the occurrence of golden standard values and golden proportion in the anterior teeth. Materials and methods. Photographs of 100 dentistry students (50 males and 50 females) were taken under standard conditions. The visible widths and lengths of maxillary right and left incisors were calculated and the ratios were compared with golden standard. Data was analyzed using SPSS 14 software. Results. Review of the results of the means showed statistically significant differences between the width ratio of right lateral teeth to the central teeth width with golden proportion (P<0.001). Likewise, the difference was significant for the left side, too (P<0.001). Test results of mean differences showed that the mean difference between proportion of right laterals to centrals with golden proportion was significant (P<0.001). The difference was significant for the left side, too (P<0.001). As a result, there is no golden proportion among maxillary incisors. The review of results of mean differences for single samples showed that the mean differences between the proportion of width-to-length of left and right central teeth was statistically significant by golden standard (P<0.001). Therefore, considering the width-to-length proportion of maxillary central teeth, no golden standard exists. Conclusion. In the evaluation of the width-to-width and width-to-length proportions of maxillary incisors no golden proportions and standards were detected, respectively.